HYBRID CONTRACT MODEL (HCM) DALAM PERSPEKTIF ETIKA BISNIS ISLAM (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The purpose of this research is to look at the Hybrid Contract Model (HCM) from the perspective of Islamic business ethics. This study uses a library research approach because the data sources come from various kinds of literature such as articles, books, books, and journals or previous research on the Hybrid Contract Model (HCM) from the perspective of Islamic business ethics (LKS). The results of the discussion The original law of a contract and its terms is valid unless it is canceled or prohibited by religion. So, as long as the Hybrid Contract Model (HCM) that is applied meets all the pillars and conditions set by Islamic law, the Hybrid Contract Model (HCM) is by Islamic business ethics which contains the values of oneness, balance, free will, responsibility, and virtue. Conversely, if in practice the Hybrid Contract Model (HCM) does not comply with the pillars, terms, and conditions of Islam, then the Hybrid Contract Model (HCM) is not fully by Islamic business ethics.